Inhibitory effect of cell-free supernatants of Pedicoccous acidilactici and Latilactobacillus sakei/Staphylococcus xylosus in combination with ethylenediaminetetraacetic acid against Escherichia coli O157:H7 strains - Incili, Gokhan Kursad; Ilhak, Osman Irfan; Calicioglu, Mehmet (Urmia Univ, 2025)
The current research was carried out to evaluate in vitro anti-microbial properties of the cell-free supernatants (CFSs) derived from Pediococcus acidilactici (PA) and Latilactobacillus sakei/ Staphylococcus xylosus (LS) against Escherichia coli O157:H7 American Type Culture Collection strains (35150, 43894, and 43985). For this purpose, the diameters of zone of inhibition of the CFSs against E. coli O157:H7 strains were measured. In addition, a time-kill assay was conducted to determine the inhibitory effect of the CFSs alone or in combination with ethylenediaminetetraacetic acid (EDTA) during incubation at 37.00 & ring;C for 24 hr. In the time-kill assay, E. coli O157:H7 was subjected to three concentrations of CFSs (1.00, 5.00, and 10.00%) and EDTA (0.02 M) in tryptic soy broth and the E. coli O157:H7 count was determined at 0, 6, and 24 hr intervals. The CFS of LS had a lower pH and higher titratable acidity compared to the PA. The CFS of LS displayed higher zones of inhibition than the CFS of PA against E. coli O157:H7 American Type Culture Collection 35150 and 43894 strains. The concentrations of 5.00 and 10.00% CFSs in combination with EDTA provided a 5.00 log10 decline in E. coli O157:H7 count over a 24-hr period. The results of this study indicated that the combination of CFSs (5.00 and 10.00%) and EDTA (0.02 M) exhibited an enhanced antibacterial effect against E. coli O157:H7 strains, which are substantial foodborne pathogenic bacteria. (c) 2025 Urmia University. All rights reserved.
Keywords: Anti-microbial activity; Cell-free supernatant; Disk diffusion; Escherichia coli O157; H7